Młody Leonardo –czyli co naprawdę wiadomo o słabych i mocnych stronach uczniów z dysleksją rozwojową - Krasowicz-Kupis, Grażyna (Neofilolog, 2011)
The paper focuses on the issue of special gifts of individuals with dyslex-ia. Many authors suggest that specific learning disabilities, like dyslexia, are connected with talents. Most often they point to the high level of vis-ual and spatial abilities. Unfortunately, the analysis of the findings of the available research shows that there is insufficient evidence that dyslexics are more creative and gifted than other people.